Documentary analysis of cases of sexual violence against boys reported in Porto Alegre - Hohendorff, Jean Von; Costa, Lucas Souza; Habigzang, Luísa Fernanda; Koller, Silvia Helena (Paidéia (Ribeirão Preto), 2014)
There are few studies regarding sexual violence (SV) against boys in Brazil. Considering this fact, the present study aimed to investigate cases reported in the General Coordination of Health Surveillance of Porto Alegre (POA GVCS) between 2009 and 2011. A total of 239 notification forms were analyzed according to: characteristics of the victim (i.e., age, race, education level, presence of disability, SV consequences); of the SV (i.e., occurrence year, notification year, notifying establishment, context, place of occurrence, type, occurrence of penetration, number of episodes, others forms of violence, number of perpetrators, final classification – whether confirmed or not – and referrals); and of the abusers (i.e., gender, relationship to the victim, use of alcohol/drugs). There was predominance of white boys between seven and 12 years of age, victims of intrafamilial SV of two or more episodes perpetrated by male perpetrators. These results can be used in planning preventive and therapeutic interventions specific to boys who are victims of SV.